Studi Kasus Prosedur Pemeriksaan Colon in Loop pada Pasien Pediatrik dengan Kasus Hirschprungs di RSUD Brebes - Abid Muhammad Fathul Islam; Ildsa Maulidya Mar'athus Nasokha; Amril Mukmin (Pusat riset dan Inovasi Nasional, 2025)
Colon In Loop examination is an important radiographic procedure in the evaluation of Hirschsprung cases in pediatric patients. At Brebes Regional Hospital, there are differences in procedures compared to existing literature, especially in the method of administering contrast media and the projections used. This study aims to review and examine the Colon In Loop examination procedure in pediatric patients with Hirschsprung cases at Brebes Regional Hospital. This study uses a qualitative descriptive approach with a case study method. Data were collected through observation, interviews, and documentation involving three radiographers and one radiologist as research subjects. Data analysis techniques were carried out through data reduction, data presentation, and drawing conclusions. Results Colon In Loop examination in pediatric patients at Brebes Regional Hospital was performed without any special preparation for the patient. Contrast media was used with a stepwise method, namely 50cc in the first stage and added 50cc in the second stage. The projections used included AP (Antero Posterior) and AP oblique to overcome visualization limitations. The Colon In Loop examination procedure at Brebes Regional Hospital differs from the literature regarding the method of contrast media insertion and additional projections. This provides better visualization for Hirschsprung's diagnosis in pediatric patients.